The Effect of Presto Cooking Time on the Organoleptic and Chemical Characteristics of Biang Shredded Fish (Setipinna breviceps) - Pratiwi, Rizkha Yana; Sukmiwati, Mery; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The objective of the research was to determine the effect presto cookingtime on the organoleptic and chemical characteristics of Shorthead hairfinanchovy shredded fish (Setipinna breviceps). The method used was experimentand composed by using completely randomized design and consisted of 4treatments, namely: A0 (biang fish with steamed), A1 (biang fish with presto time75 minutes), A2 (biang fish with presto time 90 minutes), A3 (biang fish withpresto time 105 minutes). The results showed that the best treatment was steamingbiang fish with presto for 105 minutes. The characteristics of the highestShorthead hairfin anchovy Shredded Fish quality was shown brown colored inappearance, fibrous soft and dry rustle textured, very fragrant aroma withoutputrid or rancid odor and very delicious fish and spices tasted, the compositioncontained water 5,79%, ash 5,09%, protein 31,31%, fat 19,25% and calcium330,02 mg / 100 g sample.Keywords: Shorthead hairfin anchovy, Setipinna breviceps, Presto, Shredded fish